The politics of the Palestinian Authority : from Oslo to al-Aqsa - Parsons, Nigel Craig, 1966- (Routledge, 2005)
This book is about the development of the PLO from a liberation movement to the Palestinian National Authority. It provides an up-to-date account of the situation in the Middle East, from the Palestinian political perspective.